1975
DOI: 10.1530/jrf.0.0420301
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies and Sperm Survival in the Female Tract of the Mouse and Rabbit

Abstract: Rabbit and mouse spermatozoa from male and female tracts have been examined for their species-antigenic surface character, and for adherent antibodies, by double immunofluorescence techniques. Mouse spermatozoa from the ductus deferens showed an area over the acrosome which was positive to anti-mouse serum that had been absorbed with some male mouse somatic tissues including blood, but those from the uterus and oviduct were not stained. Spermatozoa from the uterus were shown to have an antibody coat on the acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

1978
1978
1997
1997

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 14 publications
1
24
0
Order By: Relevance
“…Phagocytosis of spermatozoa in the female genital tract has been observed by several authors [4,6,7,9,16,17,201. Under the light microscope it has been demonstrated that spermatozoa are attached by their heads to microvilli of the columnar cells of animals, and that they are taken up by epithelial cells and by PMN and mononuclear cells.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Phagocytosis of spermatozoa in the female genital tract has been observed by several authors [4,6,7,9,16,17,201. Under the light microscope it has been demonstrated that spermatozoa are attached by their heads to microvilli of the columnar cells of animals, and that they are taken up by epithelial cells and by PMN and mononuclear cells.…”
Section: Discussionmentioning
confidence: 88%
“…Not much attention has been given t o a possible role of phagocytic cells in the reproductive tract in the cause of infertility. It has long been known that spermatozoa can be phagocytized or killed by a number of cell types in the vagina and uterus, including polymorphonuclear granulocytes (PMN) [4, 6,7,161, macrophages [9,201 , fibroblasts [17], and the epithelium of the vagina [17]. One author states that shortly after the arrival of spermatozoa in the uterus of the rabbit several manifestations of a normal inflammation reaction occur, such as edema, hyperemia, and infiltration of leukocytes [ 161 .…”
Section: Introductionmentioning
confidence: 99%
“…Several authors agree that IgG is probably responsible (Symons, 1967;Padma, 1972;Allen & Bourne, 1978). Cohen & Werrett (1975), using homologous sera from fertile animals to coat spermatozoa, described two populations of spermatozoa, only one of which bound immunoglobulin; they suggested that the majority, which bound IgG, were progressively impeded and phagocytosed, leaving the non-coating minority to fertilize. Johnson & Hunter (1972), using alloantibodies raised to rabbit sperm or surface coat antigens, showed that changes in binding occurred in the period between copulation and fertilization; only 10% of early uterine spermatozoa showed sperm surface antigenicity.…”
Section: Introductionmentioning
confidence: 99%
“…compared with 90% of late oviductal spermatozoa. Tyler (1977) (Cohen & Werrett, 1975) has not been experimentally investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Since most lgG-coated spermatozoa are phagocytized, it is believed that the prime function of lgG attachment is the labelling of a sperm for its destruction. (Cohen and Werrett 1975) Rapid transport of dead spermatozoa has been demonstrated in cows, pigs and rabbits (Overstreet and Tom 1982). Motility is not required for the sperm transport into the oviducts -at least not in these soecies.…”
Section: Selection and Transport Of Spermatozoamentioning
confidence: 99%